2015
DOI: 10.1371/journal.pone.0128811
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fungus Resistant Wild Accessions and Interspecific Hybrids of the Genus Arachis

Abstract: Peanut, Arachis hypogaea L., is a protein-rich species consumed worldwide. A key improvement to peanut culture involves the development of cultivars that resist fungal diseases such as rust, leaf spot and scab. Over three years, we evaluated fungal resistance under field conditions of 43 wild accessions and three interspecific hybrids of the genus Arachis, as well as six A. hypogaea genotypes. In the first year, we evaluated resistance to early and late leaf spot, rust and scab. In the second and third years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 13 publications
(16 reference statements)
3
32
0
1
Order By: Relevance
“…These progenies are of great value because they indicate potential in crossings following the breeding. In addition, the best phenotypic values coincided with the highest predicted values (BLUP) for all traits in the two generations (Tables 3 to 6), corroborating the results obtained by Michelotto et al (2015). BLUP is a function of phenotypic values that have the common objective of predicting true genetic values, and it has been used as a selection tool in various crops (Baldissera et al, 2012;Pinheiro et al, 2013;Regitano Neto, Ramos Júnior, Gallo, Freitas, & Azzini, 2013).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…These progenies are of great value because they indicate potential in crossings following the breeding. In addition, the best phenotypic values coincided with the highest predicted values (BLUP) for all traits in the two generations (Tables 3 to 6), corroborating the results obtained by Michelotto et al (2015). BLUP is a function of phenotypic values that have the common objective of predicting true genetic values, and it has been used as a selection tool in various crops (Baldissera et al, 2012;Pinheiro et al, 2013;Regitano Neto, Ramos Júnior, Gallo, Freitas, & Azzini, 2013).…”
Section: Resultssupporting
confidence: 86%
“…BLUP is a function of phenotypic values that have the common objective of predicting true genetic values, and it has been used as a selection tool in various crops (Baldissera et al, 2012;Pinheiro et al, 2013;Regitano Neto, Ramos Júnior, Gallo, Freitas, & Azzini, 2013). In peanut crop, BLUP has been used to assist the selection of lines at the early stages of breeding programs (Luz, Santos, Silva Filho, & Mello Filho, 2010) and has helped to identify sources of resistance to aerial fungal diseases and in interspecific accessions and hybrids of the genus Arachis L. (Michelotto et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data showed that accessions of A. ipaënsis and A. duranensis have higher concentrations of resveratrol than the two allotetraploids, which is a surprising result since many other studies showed differences between diploids and polyploids, the latter having better characteristics than the former (Fávero et al, 2009;Xu et al, 2014;Michelotto et al, 2015;Leal-Bertioli et al, 2015, 2017. The lack of polyploidy superiority has been previously observed for Arabidopsis thaliana and Pyrus communis, in which only a few metabolites differ between diploids and synthetic autotetraploids.…”
Section: Resveratrol Contentmentioning
confidence: 59%
“…Annual and perennial species in the section Arachis, which is considered the best adapted section, have great genetic potential for breeding with cultivated peanut (Simpson and Starr, 2001;Fávero et al 2006;Michelotto et al 2015;Fávero et al 2015b).…”
Section: Introductionmentioning
confidence: 99%